People, processes, services, and things : using services innovation to enable the Internet of everything - Dahir, Hazim; Dry, Bil.; Pignataro, Carlos (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2015)
People, Processes, Services, and Things: Using Services Innovation to Enable the Internet of Everything guides the reader through the technological advances, business needs, and societal shifts that drive the Internet of Everything (IoE). It continues by explaining the differences and relationships between the Internet of Things (IoT) and IoE. IoE offers many benefits to industries and organizations that embrace it, but there are real adoption and success barriers to address and overcome. This book discusses those barriers and offers solutions. In many cases, services are the solution because they drive IoE application and impact. The business and technical services need to deliver IoE and realize the promised benefits that are discussed in this book. Discussions include assisting candidate IoE customers to assess and rank priority gaps in business process insight, strategies to connected things, and ways to wrangle and transform data streams of new things into actionable information. The last section of this book discusses IoE applications and use cases. It includes in-depth use cases on manufacturing process changes and retail store operational improvements from customer queue management to augmented reality along with changes in security considerations, design practices, and operating procedures to ensure malicious intent does not disrupt the emerging and growing IoE networks. Knowledge of leading practices and organizational values and sensitivities are keys to successful IoE transformations. This book concludes with a complete checklist of considerations for IoE transformation success.
1. Defining the Internet of everything -- 2. Benefits and challenges of IoE -- 3. Drivers of IoE -- 4. Barriers to IoE adoption -- 5. Service innovation for IoE -- 6. IoE privacy and security -- 7. The changing world: where IoE is making the biggest difference -- 8. IoE use cases -- 9. Use case in depth, how will manufacturing benefit from IoE -- 10. Use case in depth, IoE solutions for the retail industry -- 11. Conclusions -- 12. A service industry call to action -- References -- Index.
Includes bibliographical references (page 81) and index.
Title from PDF title page (viewed on August 7, 2015).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2016. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Internet of things; Ubiquitous computing; augmented reality; cloud; data analysis; data at rest; data in motion; fog computing; innovation; Internet; Internet of Everything; IoE; Internet of Things; people; processes; service innovation; services; Electronic books